Square/factorial

Calculus Level 3

n = 0 n 2 n ! = λ e ; λ = ? \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ n^2}{n!} = \color{#3D99F6}{\lambda} e \quad ; \quad \color{#3D99F6}{\lambda} = \ ?


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Akhil Bansal
Oct 27, 2015

= n = 0 n 2 n ! = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ n^2}{n!}

= n = 0 n 2 n ( n 1 ) ! = \displaystyle\sum_{n = 0}^{\infty} \dfrac{ n^2}{n ( n - 1)!}

= n = 1 n + 1 1 ( n 1 ) ! = \displaystyle\sum_{n = 1}^{\infty} \dfrac{ n + 1 - 1}{(n - 1)!}

= n = 1 ( n 1 ( n 1 ) ! + 1 ( n 1 ) ! ) = \displaystyle\sum_{n = 1}^{\infty} \left( \dfrac{n-1}{(n-1)!} + \dfrac{1}{(n-1)!} \right)

= n = 2 1 ( n 2 ) ! + n = 1 1 ( n 1 ) ! = \displaystyle\sum_{n = 2}^{\infty} \dfrac{1}{(n - 2)!} + \displaystyle\sum_{n = 1}^{\infty} \dfrac{1}{(n - 1)!}

= ( 1 0 ! + 1 1 ! + 1 2 ! + + ) + ( 1 0 ! + 1 1 ! + 1 2 ! + + ) = \left(\dfrac{1}{0!}+ \dfrac{1}{1!} + \dfrac{1}{2!} + \ldots + \infty\right) + \left( \dfrac{1}{0!} + \dfrac{1}{1!} + \dfrac{1}{2!} + \ldots + \infty \right)

e + e = 2 e λ = 2 \large \Rightarrow e \ + \ e \ = \color{#3D99F6}{2}e \Rightarrow \boxed{\color{#3D99F6}{\lambda} = 2}

What is the General expression of n^k ? For any number k ?

For example we know that Summation (n = 0 to infinity) (n^3/n!) = 5e Summation (n = 0 to infinity) (n^4/n!) = 15e Summation (n = 0 to infinity) (n^5/n!) = 52e

Vijay Simha - 1 year, 9 months ago

e x = n = 0 x n n ! d ( e x ) d x = e x = n = 0 n x n 1 n ! d 2 ( e x ) d x 2 = e x = n = 0 ( n 2 n ) x n 2 n ! e^x = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ x^n}{n!} \\ \dfrac{d(e^x)}{dx} = e^x = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ n x^{n-1}}{n!} \\ \dfrac{d^2(e^x)}{dx^2} = e^x = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ (n^2-n) x^{n-2}}{n!}

For x = 1 x = 1 we have:

e = n = 0 1 n ! e = n = 0 n n ! e = n = 0 ( n 2 n ) n ! e = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{1}{n!} \\ e = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ n }{n!} \\ e = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ (n^2-n)}{n!}

Manipulating the last equation we obtain:

e = n = 0 ( n 2 ) n ! n = 0 ( n ) n ! e = n = 0 ( n 2 ) n ! e 2 e = n = 0 ( n 2 ) n ! e = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ (n^2)}{n!} - \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ (n)}{n!} \\ e = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ (n^2)}{n!} - e \\ 2e = \large \displaystyle\sum_{n = 0}^{\infty} \dfrac{ (n^2)}{n!}

Thus, λ = 2 \lambda = 2 .

Yours solution is quite different from traditional solutions. But it's amazing.

Adarsh Singh - 3 years, 7 months ago
Chew-Seong Cheong
Oct 26, 2016

S = n = 0 n 2 n ! = n = 1 n 2 n ! = n = 0 ( n + 1 ) 2 ( n + 1 ) ! = n = 0 n + 1 n ! = n = 0 n n ! + n = 0 1 n ! = n = 1 n n ! + n = 0 1 n ! = n = 1 1 ( n 1 ) ! + n = 0 1 n ! = n = 0 1 n ! + n = 0 1 n ! = e + e = 2 e \begin{aligned} S & = \sum_{n=\color{#3D99F6}0}^\infty \frac {n^2}{n!} \\ & = \sum_{n=\color{#D61F06}1}^\infty \frac {n^2}{n!} \\ & = \sum_{n=\color{#3D99F6}0} ^\infty \frac {(n+1)^2}{(n+1)!} \\ & = \sum_{n=\color{#3D99F6}0} ^\infty \frac {n+1}{n!} \\ & = \sum_{n=\color{#3D99F6}0} ^\infty \frac n{n!} + \sum_{n=\color{#3D99F6}0}^\infty \frac 1{n!} \\ & = \sum_{n=\color{#D61F06}1} ^\infty \frac n{n!} + \sum_{n=\color{#3D99F6}0}^\infty \frac 1{n!} \\ & = \sum_{n=\color{#D61F06}1} ^\infty \frac 1{(n-1)!} + \sum_{n=\color{#3D99F6}0}^\infty \frac 1{n!} \\ & = \sum_{n=\color{#3D99F6}0}^\infty \frac 1{n!} + \sum_{n=\color{#3D99F6}0}^\infty \frac 1{n!} \\ & = e+e=2e \end{aligned}

λ = 2 \implies \lambda = \boxed{2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...